Teenage patients with ingrown toenails: Treatment with partial matrix excision or segmental phenolization - Murat Korkmaz; Emine Çölgeçen; Yalçin Erdogan; Ahmet Bal; Kemal Özyurt (Wolters Kluwer Medknow Publications, 2013)
Background: Ingrown toenails (IT) is a very common problem leading to significant associated morbidity. The articles related to phenolization for matrix removal in teenagers with IT are not enough in the foot surgery literature. Aims: To compare the postoperative recovery periods, complication rate, and tolerability of partial matrix excision and segmental phenolization in teenagers with IT. Materials and Methods: Thirty-nine patients (13-17 years) with 48 IT were randomly divided into two groups and were treated with partial matrix excision (Group I) and segmental phenolization (Group II). We assessed the recurrence rates, postoperative complications, duration of analgesic usage, and time to return to daily activities. Results: There was no significant difference between the demographic and clinical data of the two groups. Three patients in Group I and two patients in Group II experienced moderate pain postoperatively. These patients used analgesics for 3 days. The rates of postoperative complications and recurrences between the two groups showed no statistically significant difference ( P = 0.688). The time to return to normal daily activities was significantly shorter in Group II patients than in Group I patients ( P < 0.05). Conclusions: Partial matrix excision is a very safe model of therapy in the surgical treatment of teenagers with IT. It has low recurrence rate and minimal postoperative morbidity. We concluded that segmental phenolization is also as safe as partial matrix excision in the treatment of IT and patients return to their daily activities in less time with this treatment modality.